2014
DOI: 10.3892/ijo.2014.2574
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia induces resistance to ALK inhibitors in the H3122 non-small cell lung cancer cell line with an ALK rearrangement via epithelial-mesenchymal transition

Abstract: Patients with non-small cell lung cancer (NSCLC) with echinoderm microtubule-associated protein-like 4 (EML4)-anaplastic lymphoma kinase (ALK) rearrangements generally respond to ALK inhibitors such as crizotinib. However, some patients with EML4-ALK rearrangements respond poorly to crizotinib. Hypoxia is involved in the resistance to chemotherapeutic treatments in several cancers, and we investigated the association between the responses to ALK inhibitors and hypoxia. Sensitivity of the H3122 NSCLC cell line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 35 publications
2
45
0
2
Order By: Relevance
“…Kim et al reported that long-term exposure to crizotinib induces EMT in cases of lung adenocarcinoma, causing crizotinib resistance (2). Furthermore, Kogita et al described that hypoxia induces resistance to ALK inhibitors via the EMT in NSCLC patients with ALK rearrangement (12). Based on these results, the findings in our case suggest the possibility of transformation into pleomorphic carcinoma as a result of the EMT in patients with lung cancer.…”
Section: Discussionsupporting
confidence: 60%
“…Kim et al reported that long-term exposure to crizotinib induces EMT in cases of lung adenocarcinoma, causing crizotinib resistance (2). Furthermore, Kogita et al described that hypoxia induces resistance to ALK inhibitors via the EMT in NSCLC patients with ALK rearrangement (12). Based on these results, the findings in our case suggest the possibility of transformation into pleomorphic carcinoma as a result of the EMT in patients with lung cancer.…”
Section: Discussionsupporting
confidence: 60%
“…These findings suggest that activation of MET signaling may serve as a salvage signal after alectinib treatment, which is possibly not observed in crizotinib-resistance due to the high inhibitory activity of crizotinib against MET [19,20]. As well as crizotinib-resistance, other groups have demonstrated that EGFR ligands and hypoxia-induced EMT confer resistance to alectinib [43,48]. The resistance mechanism via the bypass track has yet to be reported in ceritinib-resistant patients or cells, which should therefore be investigated in clinical and pre-clinical settings.…”
Section: Resistance Mechanisms To Alk Inhibitorsmentioning
confidence: 99%
“…With regard to the involvement of alternate signaling pathways in the acquisition of resistance to next-generation ALK inhibitors, few reports exist thus far [43,47,48,49]. In particular, the involvement of hepatocyte growth factor (HGF)/MET signaling pathway activation in the acquired resistance to alectinib has been demonstrated by several groups [47,48,49].…”
Section: Resistance Mechanisms To Alk Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations